Congenital Supravalvular and Valvular Pulmonic Stenosis in French Bulldog - มังคละพฤกษ์ ธนวัน; ชินประหัษฐ์ วรุต (Journal of Mahanakorn Veterinary Medicine, 2018)
A 2.5-month-old female French Bulldog presented at Small Animal Hospital Faculty of Veterinary Medicine Mahanakorn University of Technology because jugular pulsation was detected. On physical examination, a systolic murmur 4/6 heard best over the left heart base. Right lateral thoracic radiography showed normal heart size while ventrodorsal view demonstrated the right heart enlargement. Echocardiography revealed the right ventricular wall hypertrophy, pulmonic valve stenosis, and mild tricuspid regurgitation. Electrocardiogram was normal sinus rhythm with deep S wave. From the first visit, the severity of pulmonic stenosis was mild to moderate degree since there was no clinical sign, the veterinarian recommended to monitor every 6 months. The second visit was at the dog was about 1 year of age. The echocardiogram showed the increasing severity of pulmonic stenosis. The dog was further diagnosis by Computer Tomography (CT) scan at Small Animal Teaching Hospital Faculty of Veterinary Science, Chulalongkorn University, in order to examine the aberrant coronary arteries. The CT scan results did not find aberrant coronaries; however, supravalvular pulmonic stenosis was detected concurrent with valvular pulmonic stenosis. The further treatment with balloon valvuloplasty was suggested.